Impact of antiplatelet therapy on hemostatic plug formation in the setting of thrombocytopenia - Robert H. Lee; Abigail Ballard-Kordeliski; Summer R. Jones; Wolfgang Bergmeier (Research and Practice in Thrombosis and Haemostasis)
Background: Antiplatelet therapy (APT), mainly aspirin and P2Y12 receptor inhibitors, reduces the incidence of recurrent arterial thrombosis but also increases bleeding risk. Therefore, management of APT in patients with thrombocytopenia, itself an independent risk factor for bleeding, is a clinical challenge with few evidence-based guidelines. Data are lacking on the combined impact of thrombocytopenia and APT on hemostasis. Objectives: To systematically investigate the combined effect of thrombocytopenia and APT in mouse models of hemostasis and thrombosis. Methods: Platelet-depleted mice were repleted with donor platelets inhibited with aspirin and/or clopidogrel at low (<1 × 108/mL) or normal (>2) platelet counts. Hemostasis was assessed in the saphenous vein laser injury model, and thrombosis was assessed in the carotid artery ferric chloride model. Results: In the saphenous vein laser injury model, neither single nor dual APT significantly increased bleeding compared with vehicle at platelet counts >2 × 108/mL. However, for platelet counts <1, clopidogrel prolonged the time to the first hemostatic plug, and dual APT prolonged the time to the first plug and total bleeding time compared with vehicle and aspirin treatment. In the carotid artery ferric chloride thrombosis model, clopidogrel was entirely protected against platelet-rich thrombus formation, while aspirin had minimal effect. Conclusion: Our experimental data suggests that for severe thrombocytopenia, single APT provides an appropriate balance of antithrombotic effect and limited bleeding, with clopidogrel demonstrating a greater antithrombotic effect but slightly increased bleeding compared with aspirin.